Optical microtopographic inspection of asphalt pavement surfaces - Costa, Manuel F. M. (2017)
Microtopographic and rugometric characterization of surfaces is routinely and effectively performed non-invasively by a number of different optical methods. Rough surfaces are also inspected using optical profilometers and microtopographer. The characterization of road asphalt pavement surfaces produced in different ways and compositions is fundamental for economical and safety reasons. Having complex structures, including topographically with different ranges of form error and roughness, the inspection of asphalt pavement surfaces is difficult to perform non-invasively. In this communication we will report on the optical non-contact rugometric characterization of the surface of different types of road pavements performed at the Microtopography Laboratory of the Physics Department of the University of Minho.